Adversity Quotient as a Predictor of Early Childhood Education Teachers’ Performance amid the Challenges of Educational Digitalization - Sri Utaminingsih; Saiful Anwar; Shella Rachmawaty; Rolando P. Quinones Jr. (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study investigates the relationship between Adversity Quotient (AQ) and teacher performance among Early Childhood Education (ECE) teachers in the context of educational digitalization. Using a quantitative correlational approach, data were collected from a sample of 150 ECE teachers selected through stratified random sampling, representing formal and non-formal institutions from a population of 115 ECE schools in Serpong District, South Tangerang City, Banten. The results of the Pearson product-moment correlation test showed a very strong and significant positive correlation between AQ and teacher performance (r = 0.982, p < 0.01). These findings indicate that teachers with higher levels of psychological resilience demonstrated through persistence, control, and adaptability tend to perform better professionally. The study emphasizes the importance of integrating AQ development into teacher training programs, especially in response to the dynamic demands of digital transformation in education. Fostering AQ can enhance the sustainability and quality of teacher performance in early childhood education settings. The implications of these results highlight the strategic role of psychological preparedness in shaping effective, adaptive, and future-ready educators.